2020
DOI: 10.3390/antiox9121230
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Cocoa

Abstract: Cocoa beans are the seeds of the tropical tree Theobroma cacao L [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Factors controlling the extractability involve the kinds of solvent, the concentration of solvent, pH, temperature, irradiation time, the solid-to-solvent ratio [ 21 , 46 ], as well as the mesh size of the material particles [ 46 ]. In processing, fermentation and drying of the cocoa beans lead to oxidative degradation of polyphenols as a result of contact with the oxidative enzymes, polyphenol oxidase (PPO) and peroxidase [ 18 , 19 ]. However, accumulating studies have demonstrated that the process of determining the polyphenols content in chocolates is rather complex, it is not clear which cocoa beans are the best source of polyphenols [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors controlling the extractability involve the kinds of solvent, the concentration of solvent, pH, temperature, irradiation time, the solid-to-solvent ratio [ 21 , 46 ], as well as the mesh size of the material particles [ 46 ]. In processing, fermentation and drying of the cocoa beans lead to oxidative degradation of polyphenols as a result of contact with the oxidative enzymes, polyphenol oxidase (PPO) and peroxidase [ 18 , 19 ]. However, accumulating studies have demonstrated that the process of determining the polyphenols content in chocolates is rather complex, it is not clear which cocoa beans are the best source of polyphenols [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…During cocoa processing, the naturally occurring antioxidants (flavonoids) are lost, while others, such as Maillard reaction products, are formed. The final content of antioxidant compounds and its related antioxidant activity is in fact a function of several variables, some related to processing and formulation, while some related to the newly formed material [ 48 ], as well cited, the inherent polyphenols may also react with proteins, free amino acids, and mono- or polysaccharides during roasting to form new compounds with antioxidant activities [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive substances in cocoa pod husk are suspected responsible for these effects. Previously, polyphenolic substances found in cocoa pod husk such as flavonols (catechins, epicatechins) and proanthocyanidins have been demonstrated to lower oxidative stress products ( Oracz and Żyżelewicz, 2020 ). When the number of free radicals is reduced, the formation of ROS as a cause of cell damage (oxidative stress) will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…During cocoa processing, the waste generation is estimated at 85% of the total production, constituted by cocoa bean husks, cocoa shells, and pulp [77]. Research points to two extraction routes to obtain bioactive compounds from the residual biomass: bioconversion and solvent extraction, highlighting those with antioxidant, antimicrobial, and antiviral capacities [78] or other compounds such as polyphenols [79], pectin, phytosterols, dietary fiber, with anti-inflammatory, anti-hypertensive, anti-diabetic and anti-hypercholesterolemic properties [80]. Additionally, cocoa shell has polysaccharides, lignin, and cellulose as a dietary fiber that could be used to prepare chocolate cookies and cakes with coloration and flavor advantages over commercial products [77].…”
Section: Waste Derived From Food Industrymentioning
confidence: 99%